Influence of Water Quality on Cholesterol-Induced Tau Pathology: Preliminary Data. (15th March 2011) - Sparks, D. Larry; Ziolkowski, Chuck; Lawmaster, Todd; Martin, Timothy
Abstract : The studies employed the cholesterol-fed rabbit model of Alzheimer's disease (AD) to investigate the relationship between AD-like neurofibrillary tangle (NFT) neuropathology and tau protein levels as the main component of NFT. We measured brain and plasma tau levels and semiquantified NFT-like neuropathology in cholesterol-fed rabbits administered drinking water of varying quality (distilled, tap, and distilled+copper) compared to animals receiving normal chow and local tap water. Total tau levels in plasma were increased in all cholesterol-fed rabbits compared to animals on normal chow, regardless of quality of water. In contrast, increased tau in brain and increased AT8 immunoreactive NFT-like lesions were greatest in cholesterol-fed rabbits administered distilled water. A substantial decrease in brain tau and incidence and density of AT8 immunoreactive NFT-like lesions occurred in cholesterol-fed rabbits administered copper water, and an even greater decrease was observed in cholesterol-fed animals on local tap water. These studies suggest the possibility that circulating tau could be the source of the tau accumulating in the brain.